Preparation of a Novel Chiral Stationary Phase Containing Rhizobial Cyclic β-(1 → 2) Glucans for the Chiral Separation of Some Flavonoids - Jeong, Daham; Kim, Hwanhee; Dindulkar, Someshwar D; Lee, Jae Yung; Jung, Seunho (Bulletin of the Korean Chemical Society, 2015)
KCI Citation Count: 5